Facilitating translation activity in technical fields as a problem of computer lexicography - Купріянов, Євген Валерійович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The present article is devoted to the translation aspects of creating electronic special-purpose dictionary. By the example of the English terminology of power machine building, semantic, lexical-grammar and syntax difficulties of its translation into Ukrainian were revealed, the stages of cognitive processing of original texts by the translator (in particular the peculiarities of realizing by terms their features in texts) were characterized as well as main structural and content elements of electronic dictionary entries were determined.